2017
DOI: 10.18203/2349-2902.isj20171137
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of difficulties during laparoscopic cholecystectomy by preoperative clinical examination and ultrasonography

Abstract: Background: Cholelithiasis (gall stone disease) is a well-known disease worldwide. Ultrasonography is the most common screening test for cholecystitis and cholelithiasis. Laparoscopic Cholecystectomy is considered the treatment of choice for symptomatic gall stone disease. It is important to know the different clinical, radiological parameter and specific predictor that give some prediction of difficult LC. The aim of this study was to predict the difficulty of LC and the possibility of conversion to OC before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…10 A recent study from Israel shows a conversion rate of 5.8%. 11 In another study by Kumar et.al from Utarpardesh India shows a conversion rate of 4.5% 12 and another study from Palpa, Nepal shows a conversion rate of 6.9%. 13 When we compared our conversion rate to the local and international literature we found that our conversion rate was far less than the local and international eviedence available.…”
Section: Discussionmentioning
confidence: 91%
“…10 A recent study from Israel shows a conversion rate of 5.8%. 11 In another study by Kumar et.al from Utarpardesh India shows a conversion rate of 4.5% 12 and another study from Palpa, Nepal shows a conversion rate of 6.9%. 13 When we compared our conversion rate to the local and international literature we found that our conversion rate was far less than the local and international eviedence available.…”
Section: Discussionmentioning
confidence: 91%